2009
DOI: 10.1002/elan.200804404
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase Biosensor Based on an Hybrid Carbon Nanotube‐Conducting Polymer Modified Electrode

Abstract: A lactate biosensor constructed by immobilization of the enzyme lactate dehydrogenase (LDH) on a glassy carbon electrode modified with a hybrid material composed of the conducting polymer poly (3-methylthiophene) (P3 MT), electrodeposited on the electrode surface, and multiwalled carbon nanotubes (MWCNTs), is reported. The excellent characteristics of the electrode modified with the hybrid material toward the electrochemical oxidation of NADH allowed the construction of a robust LDH electrochemical biosensor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The modification of electrodes with carbon nanomaterials (Gasnier et al, 2013;Sun et al, 2013;Wang et al, 2012), nanoparticles Jena and Raj, 2006;Sharifi et al, 2013) or hybrid nanomaterials (Agüí et al, 2009;Govindhan et al, 2015;Hosseini et al, 2014;Mundaca et al, 2012;Teymourian et al, 2013;Tiwari and Gupta, 2014) have demonstrated to be highly successful.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The modification of electrodes with carbon nanomaterials (Gasnier et al, 2013;Sun et al, 2013;Wang et al, 2012), nanoparticles Jena and Raj, 2006;Sharifi et al, 2013) or hybrid nanomaterials (Agüí et al, 2009;Govindhan et al, 2015;Hosseini et al, 2014;Mundaca et al, 2012;Teymourian et al, 2013;Tiwari and Gupta, 2014) have demonstrated to be highly successful.…”
Section: Introductionmentioning
confidence: 97%
“…4B shows a sharp rise in the sensitivity up to 2.0x10 -3 M NAD + , with a slight decrease for higher concentrations, attributed to a slight inhibitory effect observed for higher concentrations of NAD +(Agüí et al, 2009). Therefore, 2.0x10 -3 M NAD + in solution was selected to establish the analytical characteristics of the developed biosensor.…”
mentioning
confidence: 99%
“…carbon nanotube (Agüí et al 2009), graphene (Alwarappan et al 2009) and nanoporous carbons (You et al 2011;Zhu et al 2008) to just name a few examples since the increase in the electrode active area is reported to enhance the sensitivity, selectivity and improvement of biomolecules immobilization and electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…This P3MT- MWCNT-(Naon)/GCE electrode provides fast responses, a linear range between 5.0 Â 10 À7 and 2.0 Â 10 À5 M and a detection limit of 1.7 Â 10 À7 M. The same authors developed a lactate biosensor using a similar method. 159 Both designed biosensors 158,159 showed good repeatability of the measurements, good reproducibility in the inter-biosensor assays and a good selectivity, especially when they were coated with a Naon lm. The synergistic effect of the composite constituents towards the electrocatalytic oxidation of NADH allowed the bioelectrodes to operate at low potential values without the need for redox mediators, improving the analytical performance in comparison to similar biosensors incorporating only CNTs or conducting polymers.…”
Section: 151mentioning
confidence: 99%